Beyond Trophic Factors: Exploiting the Intrinsic Regenerative Properties of Adult Neurons - Duraikannu, Arul; Krishnan, Anand; Chandrasekhar, Ambika; Zochodne, Douglas W. (Frontiers in Cellular Neuroscience, 2019)
Injuries and diseases of the peripheral nervous system are common but frequently irreversible. It is often but mistakenly assumed that peripheral neuron regeneration is robust without a need to be improved or supported. However, axonal lesions, especially those involving proximal nerves rarely recover fully and injuries generally are complicated by slow and incomplete regeneration. Strategies to enhance the intrinsic growth properties of reluctant adult neurons offer an alternative approach to consider during regeneration. Since axons rarely regrow without an intimately partnered Schwann cell, approaches to enhance Schwann cell plasticity carry along benefits to their axon partners. Direct targeting of molecules that inhibit growth cone plasticity can inform important regenerative strategies. A newer approach, a focus of our laboratory, exploits tumor suppressor molecules that normally dampen unconstrained growth. However several are also prominently expressed in stable adult neurons. During regeneration their ongoing expression ‘brakes’ growth, whereas their inhibition and knockdown may enhance regrowth. Examples have included PTEN, phosphatase and tensin homolog deleted on chromosome ten, a tumour suppressor that inhibits PI3K/pAkt signaling, Rb1, the protein involved in retinoblastoma development, and APC (adenomatous polyposis coli), a tumor suppressor that inhibits β-Catenin transcriptional signaling and its translocation to the nucleus. The identification of several new targets to manipulate the plasticity of regenerating adult peripheral neurons is exciting. How they fit with canonical regeneration strategies and their feasibility require additional work. Newer forms of nonviral siRNA delivery, may be approaches for molecular manipulation to improve regeneration.